1999
DOI: 10.1021/om980723f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Doubly Complexed Bisphosphirenyl Ether and Generation of Phosphirenylium Cations Complexed with Pentacarbonyltungsten1

Abstract: Reaction of the 1-β-chloroethyl-substituted 1H-phosphirene complex 2 with silver salts results in formation of the acceptor-substituted 1H-phosphirene complexes 3; decomposition of the latter furnishes the doubly complexed bisphosphirenyl ether 4. Treatment of the acceptor-substituted 1H-phosphirene complexes 3 or, respectively, the bisphosphirenyl ether 4 with the strong Lewis acid boron tris(trifluoromethanesulfonate) leads to the corresponding salts 6 or 7 of the pentacarbonyltungsten-substituted phosphiren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…This facile reactivity strongly supports an equilibrium between 3 and 2, as previously suggested for these compounds 12 and for other phosphine triflates. 11,18 Comparison to typical conditions for electrophilic addition by non-metal-coordinated phosphines suggests that metal coordination greatly enhances the electrophilicity, resulting in reactions that can be carried out under much milder conditions. For example, typical conditions for addition of ClPPh 2 to ferrocene using AlCl 3 are 107 °C for 24 h with 59% yield.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This facile reactivity strongly supports an equilibrium between 3 and 2, as previously suggested for these compounds 12 and for other phosphine triflates. 11,18 Comparison to typical conditions for electrophilic addition by non-metal-coordinated phosphines suggests that metal coordination greatly enhances the electrophilicity, resulting in reactions that can be carried out under much milder conditions. For example, typical conditions for addition of ClPPh 2 to ferrocene using AlCl 3 are 107 °C for 24 h with 59% yield.…”
Section: ■ Discussionmentioning
confidence: 99%
“…10 An η 1 -pentacarbonyltungsten complex, reported by Regitz et al, was prepared by abstraction of triflate from a phosphirenyl triflate complex using B(OTf) 3 in liquid SO 2 at −78 °C. 11 However, the reactivity of metal-coordinated phosphirenyl cations remained unexplored. In a recent communication, 12 we described the formation and characterization in solution of the We have shown that the phosphirenyl cation complex reacts as a metal-coordinated phosphenium ion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Species such as A (phosphirenylium ion) or B (phosphiranylium ion), which may be viewed as p-complexes of P + to alkynes or alkenes, [5] respectively (Scheme 1), have never been isolated. [6] A notable exception is the crystalline diphosphirenium ion C. [7] The dibenzo[a,d]cycloheptatrienyl (trop) platform was used for the synthesis of the highly strained dibenzophosphasemibullvalene D, [8] very robust aminophosphiranes (BABAR-Phos) E, [9] and the phosphiranium ion F (R = iPr, R 1 = tBu; Scheme 1). [10] Isolated examples of the latter are likewise rare.…”
Section: In Memory Of Pascal Le Flochmentioning
confidence: 99%
“…76 The ¢rst report of time-resolved step-scan Fourier transform infrared spectroscopy being used to obtain mechanistic information for an irreversible chemical process involved probing the reactions of the transient species [W(CO) 5 (CyH)], produced by photolysis of [W(CO) 6 ] in cyclohexane solution, with a series of incoming ligands L. 77 The preparation of a pentacarbonyltungsten complex phosphirenylium cation, 7, has been described. 78 The ¢rst molecular structures of the 1,2,4-selenadiphosphole and 1,2,4-telluradiphosphole ring systems co-ordinated in the Z 1 complexes [M(CO) 5 (P 2 SeC 2 t Bu 2 )] (M Cr or W) and [W(CO) 5 (P 2 TeC 2 t Bu 2 )] have been reported. 79 Photochemically produced nitrilium phosphine ylid tungsten complexes and their reactivity towards nitrile and alkyne derivatives have been described; the ¢rst ester-functionalised 2H-1,4,2-diazaphosphole complex, 8, which has been crystallographically characterised has also been reported.…”
Section: Chromium Molybdenum and Tungstenmentioning
confidence: 99%